Nanoscale LiNi0.5Co0.2Mn0.3O2 cathode materials for lithium ion batteries via a polymer-assisted chemical solution method. (September 2019) - Huang, Di; Shi, Yang; Tornheim, Adam P.; Bareño, Javier; Chen, Zheng; Zhang, Zhengcheng; Burrell, Anthony; Luo, Hongmei
Graphical abstract: Highlights: Nanoscale NCM with unique morphology is synthesized using polymer-assisted approach. Layered hexagonal NCM is formed with lower degree of Ni/Li cation mixing at higher calcination temperature. NCM exhibits higher discharge capacity, better cyclability and rate capability. The paper proves easy tuning compositions and particle sizes of cathode materials. Abstract: A novel and facile polymer-assisted chemical solution method is successfully developed for the synthesis of LiNi0.5 Co0.2 Mn0.3 O2 (NCM) with unique morphology and nanoparticle nature as cathodes for lithium-ion batteries. At calcination temperature up to 800 °C and 900 °C, NCM with hexagonal crystal structure of layered α-NaFeO2 ( R 3 ¯ m spacing group) is formed and a lower degree of Ni/Li cation mixing for sample heated at 900 °C is determined by XRD Rietveld refinement. SEM and TEM images reveal the uniform size distribution of nanoparticles. HRTEM confirms the single crystalline nature of particles with layered structure. XPS verifies the oxidation state of Co 3+, Mn 4+, Ni 2+ and Ni 3+ . As compared with the sample prepared at 800 °C, the sample heated at 900 °C exhibits a higher initial discharge specific capacity of 189 mAh g −1 being charged to 4.5 V at a current rate of 0.05 C, and better cyclability at 4.3 V cutoff voltage at a current density of 1 C. This method has demonstrated easy tuning compositions and particle sizes of cathode materials.